Preparation method and application of nanofiber composite carrier

By using a multi-spray blending process to add the crosslinker electrostatic spray to the electrospinning fibers during the electrospinning process, the problems of stability and structural integrity of the water-soluble polymer nanofiber immobilized enzyme were solved, and a high stability and high catalytic activity of nanofiber immobilized enzyme was prepared, achieving long-term retention of enzyme activities and the reuse of waste liquid.

CN119507126AActive Publication Date: 2025-02-25HENAN UNIVERSITY OF TECHNOLOGY
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411744208.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-02-25
Estimated Expiration
2044-11-30

AI Technical Summary

Technical Problem

The nanofiber immobilized enzymes prepared by existing water-soluble polymers have defects in stability and structural integrity, resulting in their soluble in water and damage to the fiber membrane structure.

Method used

During the electrospinning process, a crosslinking agent is added to the electrospinned fibers in the form of electrostatic spray to achieve crosslinking of the fibers without destroying their structure, thereby preparing nanofiber immobilized enzymes with high stability, good biocompatibility and high catalytic activity.

Benefits of technology

The high stability and good structural integrity of nanofiber immobilized enzymes are achieved, the enzyme activity and retention rate of reusable enzyme activity are improved, and the problem of reuse of waste liquid in viscose fiber production process is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507126A_ABST
    Figure CN119507126A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nanofiber composite carrier. A blending method is adopted, polyvinyl alcohol and waterborne polyurethane are blended to prepare a nanofiber membrane, electrostatic spraying is combined, a cross-linking agent is introduced, the mechanical performance of the membrane is further enhanced, and the nanofiber composite carrier with good biocompatibility is obtained. And preparing the nanofiber immobilized enzyme by using an adsorption method, wherein the immobilized enzyme has good catalytic activity and handling stability. For example, after the immobilized hemicellulase is repeatedly used for multiple times, 80.3% of the enzyme activity of the first time is still reserved at the eighth time. After the immobilized cellulase is repeatedly used for multiple times, 86.1% of the first enzyme activity is still reserved at the eighth time. The composite carrier disclosed by the invention has a relatively good application effect in the field of immobilized enzymes, realizes recycling of waste liquid in a viscose fiber production process, and has a good application prospect in industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of immobilized enzymes, and relates to a preparation method of an electrostatic spinning nanofiber composite carrier and application of the same in immobilized enzymes. Background Art

[0002] Xylanase is a type of enzyme system that degrades xylan. It hydrolyzes xylan into xylo-oligosaccharides, including xylobiose, xylotriose and other oligosaccharides, and a small amount of arabinose by hydrolyzing the β-1,4-glycosidic bonds of xylose molecules. Hemicellulase is a complex enzyme system, mainly including xylanase and mannanase, which also has a degrading effect on xylan. Cellulose can promote the dissolution of plant cell walls, promote the release of hemicellulose while hydrolyzing cellulose, and is conducive to the subsequent hydrolysis and preparation of oligosaccharides. Xylanase, hemicellulase and cellulase are often used to hydrolyze lignocellulose, prepare high value-added products, and realize the green conversion of lignocellulose. However, free enzymes have disadvantages such as difficulty in recovery and poor stability, which leads to increased use costs. Immobilized enzymes have the characteristics of easy recovery, reusability, and good stability, which make up for the defects of free enzymes.

[0003] Among the various materials for immobilizing enzymes, nanomaterials have the advantages of high specific surface area, multiple attachment sites, and good biocompatibility, and have attracted extensive attention from researchers. However, powdered or granular nanomaterials are not easy to separate and recycle in the reaction system, and then form new impurities, which limits the application of immobilized enzymes. Nanofiber membranes not only have a nanostructure at the microscopic level, but also have continuity at the macroscopic level. As an excellent immobilization carrier, electrospun nanofibers have become a research hotspot for immobilized enzymes, and have good application prospects in the field of immobilized enzymes.

[0004] In recent years, many processes for immobilizing enzymes on nanofibers have been developed at home and abroad. For example, Niu et al. disclosed a method for fixing laccase on polylactic acid electrospun fibers. Polylactic acid fibers have good biocompatibility, are easily degradable and do not produce secondary pollution. Liu et al. disclosed a method for preparing composite fibers, preparing polypeptides into nanofibers, grafting them on poly(glycidyl methacrylate-co-methyl acrylate) electrospun fibers, and improving enzyme fixation performance and film-forming properties. These studies have shown that the unique structure of electrospun nanofibers enables them to achieve good results in the field of immobilized enzymes, and this application document uses polyvinyl alcohol and water-based polyurethane blends to prepare composite materials, and achieves beneficial effects on the immobilization of hydrolases. Zong et al. used electrospinning and electrostatic spraying synchronization to wrap polysulfone and polyurethane around graphene oxide nanosheets to prepare elastic three-dimensional fiber sponges with noise reduction functions, verifying the feasibility and unique effects of combining electrospinning with electrospraying. While preparing composite fibers by electrospinning, this application document forms smiling droplets attached to the fibers by means of electrospraying, and the prepared materials not only have good hydrophilicity, biocompatibility and stability. Luo et al. disclosed a method for preparing magnetic chitosan microspheres immobilized enzymes. The immobilized proteases and amylases achieved beneficial effects in sludge hydrolysis. Fan et al. disclosed a method for immobilizing naringinase on polyurethane nanofiber membranes. The prepared immobilized enzyme can be reused many times and can effectively hydrolyze naringin and remove bitter substances. Related studies have shown that immobilized hydrolases can effectively improve the stability of the enzyme while maintaining the hydrolytic activity of the enzyme, have good storage stability, and have good application prospects in the field of food processing.

[0005] Existing studies have shown excellent performance of nanofiber-immobilized enzymes prepared using water-insoluble polymers, but the application of electrospun fiber-immobilized enzymes using polyvinyl alcohol-based water-soluble polymers is still very limited. Nanofibers have poor stability and are easily soluble in water, which needs to be resolved. Soaking the fibers in a crosslinker solution can reduce solubility, but the fiber membrane structure will still be damaged. Therefore, a new multi-nozzle blending process is studied. During the electrospinning process, the crosslinker is added to the electrospun fibers in the form of an electrostatic spray to complete crosslinking without destroying the fiber structure. Rapid preparation of nanofiber-immobilized enzymes with high stability, good biocompatibility, and high catalytic activity is a key technical problem that technicians in this field need to solve. Summary of the invention

[0006] The present invention provides a preparation method of a nanofiber composite carrier and application thereof. The reagents used in the present invention are from a reagent company.

[0007] The technical solution adopted by the present invention is: A method for preparing a nanofiber composite carrier, comprising the following steps: (1) Mix polyvinyl alcohol and distilled water in a certain proportion, heat in a boiling water bath and stir continuously until fully dissolved, filter with gauze and cool to room temperature to obtain a polyvinyl alcohol aqueous solution; (2) Take a certain volume of the polyvinyl alcohol solution in (1), add a certain amount of surfactant, dilute with water to dissolve, stir for 4-8 hours, ultrasonicate at room temperature for 10-30 minutes and then stand to obtain a polyvinyl alcohol spinning solution; (3) Take a certain mass of the polyvinyl alcohol solution in (1), add a certain amount of aqueous polyurethane, dilute with water and stir for 4-8 hours to obtain a polyvinyl alcohol-aqueous polyurethane spinning solution; (4) Take a certain mass of cross-linking agent and dissolve it in water, add a certain mass of polyvinyl pyrrolidone, stir and dissolve to obtain a cross-linking solution; (5) Transfer the prepared spinning solution and cross-linking solution to a 2.5-10 mL syringe with a needle inner diameter of 0.63-0.90 mm, place it horizontally in a four-unit propulsion pump, electrospin at a temperature of 20-30°C and a humidity of 40-70%, and dry it in an oven at 40-50°C for 12-24 hours. h; (6) placing the nanofiber membrane in glutaraldehyde vapor for 4 to 8 h and washing it with distilled water for multiple times to obtain a nanofiber composite carrier.

[0008] Furthermore, the concentration of the polyvinyl alcohol after dilution in (2) is 5-13%, the surfactant is preferably one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, and Tween-20, and the ratio of the surfactant to the polyvinyl alcohol is 0.2 / 1-0.8 / 1 g / g.

[0009] Furthermore, the ratio of the aqueous polyurethane to the polyvinyl alcohol in (3) is 1.25 / 1 to 1.5 / 1 g / g.

[0010] Furthermore, the cross-linking agent in (4) is preferably at least one of borax, boric acid, glyoxal and glutaraldehyde, and the ratio of the cross-linking agent to polyvinyl pyrrolidone is 0.7 / 1 to 1.8 / 1 g / g.

[0011] Furthermore, the spinning process parameters in (5) are as follows: positive high voltage 13~19 kV, negative high voltage 0~-2 kV, propulsion speed 0.03~0.05 mm / min, translation speed 80~100 mm / min, the distance between the needle and the receiving device is 10~15 cm, the receiving device is a receiving roller wrapped with release paper, and the receiving roller receiving speed is 40~60 r / m.

[0012] Furthermore, the glutaraldehyde vapor in (6) is preferably saturated vapor.

[0013] Furthermore, in the nanofiber composite carrier, the diameter of the electrospun fibers is hundreds of nanometers, and the water-based polyurethane is distributed on the fiber surface.

[0014] The invention also discloses application of the composite carrier prepared by the method in immobilized enzyme.

[0015] Furthermore, the composite carrier is immersed in an enzyme buffer solution, placed on a shaker and shaken for 30 to 50 minutes, taken out and washed with a buffer solution to obtain a nanofiber-immobilized enzyme.

[0016] Furthermore, in the enzyme buffer solution, the buffer is preferably at least one of phosphate buffer, acetate buffer, and citrate buffer, the buffer pH is preferably 4-6, the buffer concentration is preferably 0.01-0.20 mol / L, the enzyme concentration is 1-10 mg / mL, and the enzyme is preferably at least one of hemicellulase, xylanase, and cellulase.

[0017] Furthermore, the substrates of nanofiber-immobilized xylanase and nanofiber-immobilized hemicellulase are one or more of corncob xylan, straw xylan, coconut shell xylan and viscose fiber xylan; and the substrate of nanofiber-immobilized cellulase is cellulose.

[0018] Furthermore, the viscose fiber xylan preparation process is to take 50-100 mL of hemicellulose extract, add three times the volume of 95% ethanol, let it stand overnight, take out the solid after filtration, wash the solid with 95% ethanol and then dry it to obtain the alcohol precipitation product xylan, and recover the ethanol by rotary evaporation of the filtrate.

[0019] Furthermore, the method for using the nanofiber-immobilized enzyme is as follows: the substrate is dissolved in a phosphate buffer solution with a pH of 5 to 6, and the substrate concentration is preferably 0.5% to 5%. The immobilized enzyme is added, and the mixture is oscillated at a constant temperature of 50° C. for 0.5 to 4 h, the immobilized enzyme is removed, and the supernatant is collected for later use.

[0020] Furthermore, the reducing sugar content determination method (DNS method) was as follows: 2 mL of the test solution was added to 2 mL of DNS solution, boiled in a boiling water bath for 2 min, and the absorbance was measured at 540 nm after dilution 10 times, and a standard curve was prepared using glucose as the standard.

[0021] Furthermore, the enzyme activity is defined as follows: the number of micromoles of reducing sugar released from the substrate solution by hydrolysis of 1 g of immobilized enzyme at 50°C per minute. The calculation formula is as follows: (1) Where: V--solution volume, mL; C0--reducing sugar concentration of solution, mg / mL; M--reducing sugar molar mass, g / mol; t--enzymatic reaction time, min; m--mass of immobilized enzyme, g.

[0022] The present invention is beneficial in that: The composite fiber composed of three kinds of fibers is collected at the same time by using four-piece blending, namely polyvinyl alcohol, which constitutes the fiber membrane; 4% polyvinyl alcohol-waterborne polyurethane, the fiber with waterborne polyurethane plays an adhesion role; saturated boric acid-polyvinyl pyrrolidone, which forms a fine spray in the electric field, so that the polyvinyl alcohol fibers are cross-linked with each other to obtain a nanofiber mat with a certain thickness. The nanofiber prepared by the present invention has a small diameter, a large specific surface area, good hydrophilicity, and good mechanical strength. The prepared immobilized enzyme has high activity and stability, and the waste liquid of the viscose fiber production process is reused. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Statistical diagram of enzyme activity retention rate of immobilized hemicellulase after multiple times of use.

[0024] Figure 2 This is a statistical diagram of enzyme activity retention rate after multiple uses of immobilized cellulase. DETAILED DESCRIPTION

[0025] The following examples are used to further illustrate the present invention, but are not intended to limit the scope of the present invention.

[0026] Example 1 Preparation of nanofiber composite carrier and application of immobilized xylanase 7-8 g of polyvinyl alcohol was mixed with distilled water, heated in a boiling water bath and stirred continuously until fully dissolved, filtered with gauze and cooled to room temperature to obtain an 8-13% polyvinyl alcohol aqueous solution; (2) the polyvinyl alcohol solution in step (1) was added with hexadecyltrimethylammonium chloride, diluted and dissolved with water, stirred for 4-6 h, ultrasonicated at room temperature for 20-30 min and then allowed to stand to obtain a polyvinyl alcohol spinning solution containing 4-6% hexadecyltrimethylammonium chloride; (3) the polyvinyl alcohol solution in step (1) was added with aqueous polyurethane, diluted and stirred for 4-6 h to obtain a 3% polyvinyl alcohol-4% aqueous polyurethane spinning solution; (4) 0.9-1.0 g of boric acid was dissolved in 10 mL of water, 1.0 g of polyvinyl pyrrolidone was added, stirred and dissolved to obtain a cross-linking solution; (5) the prepared spinning solution and cross-linking solution were transferred to a 2.5-5 mL syringe with a needle inner diameter of 0.63-0.80 mm, placed horizontally in a quadruple propulsion pump, and the positive high pressure was adjusted to 15-17 kV, negative high voltage -2 kV, propulsion speed 0.03~0.05 mm / min, translation speed 80~100 mm / min, the distance between the needle and the receiving device is 10~12 cm, the receiving device is a receiving roller wrapped with release paper, the receiving roller receiving speed is 50~60 r / m, electrospinning is carried out in an environment of temperature 20~30℃ and humidity 40~70%, and drying in an oven at 45~50℃ for 12~15 h; (6) the dried nanofiber membrane is placed in saturated glutaraldehyde vapor for cross-linking for 6~8 h, and washed with distilled water to obtain a nanofiber composite carrier.

[0027] The composite carrier was immersed in a xylanase buffer solution with a concentration of 8-10 mg / mL, the buffer was a phosphate buffer solution with a pH of 4-60.01-0.1 mol / L, and was placed on a shaker for 30-50 min. After being taken out and washed with the buffer, nanofiber-immobilized xylanase was obtained.

[0028] Dissolve viscose fiber xylan in a phosphate buffer solution with a pH of 5-6 to prepare a xylan solution with a concentration of 0.5-1%, add immobilized xylanase, and keep it in a 50℃ water bath for 30-60 min. Remove the immobilized enzyme and take the enzymatic supernatant to detect the reducing sugar content.

[0029] The yield, expressed as the total amount of reducing sugars (mg) obtained by enzymatic hydrolysis per gram of alcohol precipitated solids (g), was 231.72 mg / g.

[0030] Example 2 Preparation of nanofiber composite carrier and application of immobilized hemicellulase 10-12 g of polyvinyl alcohol was mixed with distilled water, heated in a boiling water bath and stirred continuously until fully dissolved, filtered with gauze and cooled to room temperature to obtain an 8-13% polyvinyl alcohol aqueous solution; (2) the polyvinyl alcohol solution in step (1) was added with hexadecyltrimethylammonium bromide, diluted and dissolved with water, stirred for 6-8 h, ultrasonicated at room temperature for 20-30 min and then allowed to stand to obtain a polyvinyl alcohol spinning solution containing 4-6% hexadecyltrimethylammonium bromide; (3) the polyvinyl alcohol solution in step (1) was added with aqueous polyurethane, diluted and stirred for 4-6 h to obtain a 4% polyvinyl alcohol-5% aqueous polyurethane spinning solution; (4) 0.9-1.2 g of boric acid was dissolved in 10 mL of water, 1.2 g of polyvinyl pyrrolidone was added, stirred and dissolved to obtain a cross-linking solution; (5) the prepared spinning solution and cross-linking solution were transferred to a 2.5-10 mL syringe with a needle inner diameter of 0.70-0.80 mm, placed horizontally in a quadruple propulsion pump, and the positive high pressure was adjusted to 17 kV, negative high voltage -2 kV, propulsion speed 0.04~0.05 mm / min, translation speed 80~100 mm / min, the distance between the needle and the receiving device is 10~14 cm, the receiving device is a receiving roller wrapped with release paper, the receiving roller receiving speed is 50~60 r / m, electrospinning is carried out in an environment of temperature 20~30℃ and humidity 40~70%, and drying in an oven at 40~50℃ for 12~15 h; (6) the dried nanofiber membrane is placed in saturated glutaraldehyde vapor for cross-linking for 6~8 h, and washed with distilled water to obtain a nanofiber composite carrier.

[0031] The composite carrier was immersed in a hemicellulase buffer solution with a concentration of 8-10 mg / mL, the buffer was a phosphate buffer solution with a pH of 4-60.1-0.15 mol / L, and was placed on a shaker for 30-50 min. After being taken out and washed with the buffer, the nanofiber-immobilized hemicellulase was obtained.

[0032] Dissolve corncob xylan in a phosphate buffer solution with a pH of 5-6 to prepare a xylan solution with a concentration of 0.5-1%. Add immobilized hemicellulase and keep it in a 50°C water bath for 30-60 min. Take out the immobilized hemicellulase and measure the enzyme activity. Repeat this process. After the nanofiber-immobilized hemicellulase was reused 8 times, the enzyme activity retention rate was 80.3%. Figure 1 .

[0033] Example 3 Preparation of nanofiber composite carrier and application of immobilized cellulase (1) Mix 10-12 g of polyvinyl alcohol with distilled water, heat in a boiling water bath and stir continuously until fully dissolved, filter with gauze and cool to room temperature to obtain an 8-13% polyvinyl alcohol aqueous solution; (2) Take the polyvinyl alcohol solution in step (1), add hexadecyltrimethylammonium bromide, dilute and dissolve with water, stir for 6-8 h, ultrasonicate at room temperature for 20-30 min and then stand to obtain a polyvinyl alcohol spinning solution containing 4-6% hexadecyltrimethylammonium bromide; (3) Take the polyvinyl alcohol solution in step (1), add aqueous polyurethane, dilute and stir for 4-6 h to obtain a 4% polyvinyl alcohol-5% aqueous polyurethane spinning solution; (4) Take 0.9-1.2 g of boric acid and dissolve it in 10 mL of water, add 1.2 g of polyvinyl pyrrolidone, stir and dissolve to obtain a cross-linking solution; (5) Transfer the prepared spinning solution and cross-linking solution to a 2.5-10 mL needle with an inner diameter of 0.70-0.80 mm The nanofiber membrane was placed in a syringe with a diameter of 1 mm and placed horizontally in a four-unit propulsion pump. The positive high voltage was adjusted to 17 kV, the negative high voltage was adjusted to -2 kV, the propulsion speed was 0.04~0.05 mm / min, the translation speed was 80~100 mm / min, the distance between the needle and the receiving device was 10~14 cm, the receiving device was a receiving roller wrapped with release paper, and the receiving speed of the receiving roller was 50~60 r / m. Electrospinning was carried out in an environment with a temperature of 20~30℃ and a humidity of 40~70%, and then dried in an oven at 40~50℃ for 12~15 h. (6) The dried nanofiber membrane was placed in saturated glutaraldehyde vapor for cross-linking for 6~8 h, and washed with distilled water to obtain a nanofiber composite carrier.

[0034] The composite carrier was immersed in a cellulase buffer solution with a concentration of 8-10 mg / mL, the buffer was a phosphate buffer solution with a pH of 4-60.1-0.15 mol / L, and was placed on a shaker for 30-50 min. After being taken out and washed with the buffer, nanofiber-immobilized cellulase was obtained.

[0035] Add cellulose to a phosphate buffer solution with a pH of 5-6, prepare a substrate solution with a concentration of 0.5-1%, add immobilized cellulase, keep it in a 50℃ water bath for 30-60 min, take out the immobilized cellulase, and measure the enzyme activity. Repeat this process. After the nanofiber immobilized cellulase was reused 8 times, the enzyme activity retention rate was 86.1%. For details, see Figure 2 .

Claims

1. A method for preparing a nanofiber composite carrier, characterized in that: The following steps are involved: (1) Mix polyvinyl alcohol and distilled water in a certain proportion, heat in a boiling water bath and stir continuously until fully dissolved, filter with gauze and cool to room temperature to obtain a polyvinyl alcohol aqueous solution; (2) Take a certain volume of the polyvinyl alcohol solution in (1), add a certain amount of surfactant, dilute with water to dissolve, stir for 4-8 hours, ultrasonicate at room temperature for 10-30 minutes and then stand to obtain a polyvinyl alcohol spinning solution; (3) Take a certain mass of the polyvinyl alcohol solution in (1), add a certain amount of aqueous polyurethane, dilute with water and stir for 4-8 hours to obtain a polyvinyl alcohol-aqueous polyurethane spinning solution; (4) Take a certain mass of cross-linking agent and dissolve it in water, add a certain mass of polyvinyl pyrrolidone, stir and dissolve to obtain a cross-linking solution; (5) Transfer the prepared spinning solution and cross-linking solution to a 2.5-10 mL syringe with a needle inner diameter of 0.63-0.90 mm, place it horizontally in a four-unit propulsion pump, electrospin at a temperature of 20-30°C and a humidity of 40-70%, and dry it in an oven at 40-50°C for 12-24 hours. h; (6) placing the nanofiber membrane in glutaraldehyde vapor for 4 to 8 h and washing it with distilled water for multiple times to obtain a nanofiber composite carrier.

2. The method for preparing a nanofiber composite carrier according to claim 1, characterized in that: The concentration of the polyvinyl alcohol after dilution in (2) is 5-13%, the surfactant is preferably one or more of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, Tween-20, and the ratio of the surfactant to the polyvinyl alcohol is 0.2 / 1-0.8 / 1 g / g.

3. The method for preparing a nanofiber composite carrier according to claim 1, characterized in that: The ratio of aqueous polyurethane to polyvinyl alcohol in (3) is 1.25 / 1 to 1.5 / 1 g / g.

4. The method for preparing a nanofiber composite carrier according to claim 1, characterized in that: The cross-linking agent in (4) is preferably at least one of borax, boric acid, glyoxal and glutaraldehyde, and the ratio of the cross-linking agent to polyvinyl pyrrolidone is 0.7 / 1-1.8 / 1 g / g.

5. The method for preparing a nanofiber composite carrier according to claim 1, characterized in that: The spinning process parameters in (5) are as follows: positive high voltage 13~19 kV, negative high voltage 0~-2 kV, propulsion speed 0.03~0.05 mm / min, translation speed 80~100 mm / min, the distance between the needle and the receiving device is 10~15 cm, the receiving device is a receiving roller wrapped with release paper, and the receiving roller receiving speed is 40~60 r / m.

6. The nanofiber composite carrier according to claim 1, characterized in that: In the nanofiber composite carrier, the diameter of the electrostatically spun fiber is hundreds of nanometers, and the water-based polyurethane is distributed on the fiber surface.

7. Use of the composite carrier obtained by the preparation method according to claim 1 in immobilized enzyme.

Citation Information

Patent Citations

  • Preparation method of immobilized enzyme

    CN104404021A

  • Hydrolysis-resistant electrospinning PVA / glutaraldehyde crosslinked nanofiber film and preparation method thereof

    CN108456934A

  • Structure-enhanced hydrotalcite-immobilized composite fiber membrane and preparation method and application thereof

    CN111359452A

  • Method for immobilizing enzyme on nanofibers

    CN111876405A

  • Fiber composite warm-keeping flocculus and preparation method thereof

    CN112981712A